Intimate interventions in global health family planning and HIV prevention in sub-Saharan Africa - Robinson, Rachel Sullivan (Cambridge University Press, 2019)
When addressing the factors shaping HIV prevention programs in sub-Saharan Africa, it is important to consider the role of family planning programs that preceded the epidemic. In this book, Rachel Sullivan Robinson argues that both globally and locally, those working to prevent HIV borrowed and adapted resources, discourses, and strategies used for family planning. By combining statistical analysis of all sub-Saharan African countries with comparative case studies of Malawi, Nigeria, and Senegal, Robinson also shows that the nature of countries' interactions with the international community, the strength and composition of civil society, and the existence of technocratic leaders influenced variation in responses to HIV. Specifically, historical and existing relationships with outside actors, the nature of nongovernmental organizations, and perceptions of previous interventions strongly structured later health interventions through processes of path dependence and policy feedback. This book will be of great use to scholars and practitioners interested in global health, international development, African studies and political science